The Risk of Developing Constipation After Neonatal Necrotizing Enterocolitis - Chen, Shan-Ming; Huang, Jing-Yang; Wu, Ming-Chi; Chen, Jia-Yuh (Frontiers in Pediatrics, 2020)
Background: Neonatal necrotizing enterocolitis (NEC) is a complex and lethal inflammatory bowel necrosis that primarily affects premature infants. Gut dysbiosis has been implicated in the pathogenesis of NEC. We aim to assess the association between NEC and two other diseases in children, including allergic diseases and constipation, considered to be associated with the alterations in gut microbiota composition. Methods: This retrospective population-based cohort study was conducted using the Taiwan Birth Registration Database, Birth Certificate Application, and National Health Insurance Research Database to inter-link the medical claims of neonates and their mothers. A total of 2,650,634 delivery events were retrieved from 2005 to 2015. We identified a NEC cohort and selected a comparison cohort according to propensity score matching (1:1). Cox proportional hazard regression models were used to determine possible associations of predictors and to obtain adjusted hazard ratios (aHRs). Results: A total of 1,145 subjects in the NEC cohort and 1,145 subjects in the matched cohort were analyzed during the observation period. No significant difference was observed in the incidence of allergic diseases between the two groups. NEC patients had a significant 30.7% increased risk of developing constipation (aHR=1.307; 95% CI 1.089–1.568). The cumulative incidence of constipation was significantly higher in the NEC cohort than in the matched cohort by the end of follow-up (log-rank test P=0.003) Conclusion: Infants with NEC have a significantly higher incidence rate of developing constipation but no increased risk of allergic diseases. This suggests that inflammation and subsequent pathologic changes occurring in NEC may have a long-term effect on intestinal motility and an impact on the risk of constipation.